Development of a Microlearning-Based Instructional Model for Higher Education: The MICROS Framework - Widyaningrum, Retno; Situmorang, Robinson; Sukardjo, Mochammad (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study aimed to develop a microlearning-based instructional model, termed MICROS (Microlearning Systematic Operational Steps), to support structured, pedagogically grounded learning processes in higher education. The development process integrated the Dick and Carey instructional design framework with the 4D development model (Define, Design, Develop, Disseminate) to produce a systematic model that guides educators in designing, implementing, and evaluating microlearning-based courses. The model was developed within the context of the Perception and Message Design course at a public university in Indonesia. A formative evaluation was conducted involving four domain experts: two instructional design experts, one media expert, and one material expert. Evaluation instruments employed a Likert-scale questionnaire assessing multiple dimensions, including instructional coherence, digital media integration, content quality, assessment design, flexibility, and accessibility. Results indicate that the MICROS model achieved high feasibility ratings across all expert evaluations. The first instructional design expert assigned a score of 60 out of 60 (Very Good), the media expert scored 60 out of 60 (Very Good), and the material expert scored 45 out of 45 (Very Good), while the second instructional design expert assigned a score of 42 out of 60 (Good). The MICROS model offers a structured six-stage instructional sequence — Map, Identify, Create, Respond, Operate, and Summarise — that systematically integrates microlearning principles with established instructional design processes. The model supports Sustainable Development Goal 4 (SDG 4) by promoting equitable access to quality higher education through flexible, technology-enabled learning environments. These findings suggest that the MICROS framework is a feasible, theoretically grounded approach to implementing microlearning in higher education contexts.